Website Sistem Informasi Pencatatan Infaq Di MA Baiturrahman Banyuwangi - Aidina, Eca; Alfiyan, Faruk (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2025)
Previously, the infaq recording process at MA Baiturrahman Banyuwangi was conducted manually, which often led to data inaccuracies and delays in information recap. This study aims to develop a web-based infaq information system to improve data accuracy and management efficiency. The development method used is the waterfall model, as it offers a structured approach suitable for system with well-defined requirements from the outset. The technologies implemented include PHP, MySQL, HTML, adn CSS. The system provides login features with two user roles (admin and user), infaq data management based on class levels (10, 11, and 12), data filtering by month and year, and report printing. Admins have full acces to manage data, while users are limited to adding and printing data. System testing was conducted using the Black Box method to ensure each feature functions as intended. Based on the research findings, the implementation of this system has proven effective in recuding recording errors, speeding up data recap processes, and enhacing the overall efficiency of infaq management at MA Baiturrahman Banyuwangi.